Primary Malignant Lymphoma of Cervix: A Case Report - Laila Mousavi Seresht; Zohreh Yousefi; Behrouz Davachi; Amir Hosein Jafarian; Mansoureh Mottaghi; Helena Azimi; Mojgan Soltani; Yasaman Nikooiyan; Tahereh Zavary (Mashhad University of Medical Sciences, 2019)
Background:Primary malignant lymphoma of the uterine cervix is extremely rare and can be misdiagnosed due to its different clinical presentations. The aim of this report was to introduce a case of primary malignant lymphoma of the uterine cervix which was misdiagnosed as an ovarian cyst on ultrasonography. Case report: A 31-year-old female referred with a chief complaint of abnormal uterine bleeding. The ultrasound findings showed a suspicious malignant ovarian mass and the examinations demonstrated a large cervical mass which was considered as stage IB2 in the clinical staging of cervical cancer. However, a biopsy confirmed the presence of non-Hodgkin's B cell lymphoma of the cervix. Systemic chemotherapy followed by CHOP regimen (cyclophosphamide, adriamycin, vincristine, added to rituximab and prednisolone) was started based on the diagnosis. On the 14th month of serial follow-up, the patient was disease-free with no signs of a recurrence. Conclusion: A pelvic examination in patients with vaginal bleeding, vaginal discharge, and pelvic discomfort should be considered as the first step after taking the patient's medical history.